Growth, leaf nutrient concentration and photosynthetic nutrient use efficiency in tropical tree species planted in degraded areas in central Amazonia - dos Santos, Ulysses Moreira; Gonçalves, José Francisco de Carvalho; Feldpausch, Ted R. (Forest Ecology and Management, 2006)
The success of initial tree seedling establishment is related to the capture and use of primary resources such as light and nutrients. The selection of tree species with a greater potential to assimilate carbon and capacity to efficiently utilize nutrients and light would facilitate the revegetation of degraded areas, primarily where irradiance is high and soil nutrient availability low. We analyzed soil physical and chemical characteristics, survival, growth, photosynthesis, chlorophyll a fluorescence, leaf macro- and micro-nutrient content and photosynthetic nutrient use efficiency in young tropical tree species planted in degraded areas in central Amazonia. The species studied were: Bellucia grossularioides, Bombacopsis macrocalyx, Cecropia ficifolia, Cecropia sciadophylla, Chrysophyllum sanguinolentum, Eugenia cumini, Inga edulis and Iryanthera macrophyla. C. sanguinolentum, a late secondary species, exhibited the lowest survival rates, except when compared with B. grossularioides and C. sciadophylla. Photosynthesis varied between 34 and 264 nmol g-1 s-1 for the eight species; species of Cecropia had photosynthetic values eight times greater than C. sanguinolentum. For the photochemical efficiency of photosystem II, C. sanguinolentum presented the highest degree of photoinhibition as a result of an inefficient use of excess irradiance. Leaf macronutrient concentrations varied from 16 to 29, 0.4 to 1.0, 6 to 13, 7 to 22, 1.6 to 3.4 g kg-1 for N, P, K, Ca and Mg, respectively. For photosynthetic nutrient use efficiency, in general, the two species of Cecropia exhibited the highest values, while C. sanguinolentum presented the lowest macronutrient use efficiency. The two species of Cecropia had photosynthetic nitrogen use efficiency seven times greater than C. sanguinolentum. On these highly degraded soils we found that pioneer trees (Cecropia) are better able to colonize than species from other successional stages. Trees on these degraded soils are primarily limited by P or micronutrients. Despite the remove of the O horizon, N does not appear to limit photosynthetic activity. From this we conclude that species of Cecropia possess ecophysiological mechanisms associated with carbon assimilation and nutrient use that determines success in early establishment and has potential to recuperate degraded areas, especially when compared to C. sanguinolentum. Early secondary species such as I. edulis and E. cumini could also be used with success in forest plantings to recuperate degraded areas when selecting for species, (1) efficient in the utilization of excess energy for photosynthesis, (2) efficient in the use of limited soil nutrients and (3) with high survival and growth rates. © 2006 Elsevier B.V. All rights reserved.
Keywords: Chlorophyll; Fluorescence; Nutrition; Photosynthesis; Seed; Forest Succession; Specific Leaf Area; Survival Rate; Forestry; Chlorophyll; Fluorescence; Growth; Photoinhibition; Photosynthesis; Soil Nutrient; Species Diversity; Tropical Forest; Chlorophylls; Fluorescence; Forestry; Nutrition; Amazonia; South America; Bellucia; Bombacopsis; Cecropia; Cecropia Sciadophylla; Chrysophyllum Sanguinolentum; Eugenia; Inga Edulis; Iryanthera; Syzygium Cumini